PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PT MITRA ENERGI PERSADA TBK DI BURSA EFEK INDONESIA - Rahmatullah, Bill Hilton; Mulyati, M.M, Dra. Diana Juni; Pratiwi, M.M, Dra. Ni Made Ida (Research Journal of Social Science and Economics, 2025)
The purpose of this study was to determine the effect of profitability and firm value on PT Mitra Energi Persada Tbk. This research method uses a quantitative descriptive method, while the data source used is quarterly financial reports from 2018-2022. The population used in this research is all financial statement data of PT Mitra Energi Persada Tbk. sample determined by purposive sampling technique, with certain criteria. The research data used in this study is secondary data obtained from the official website of PT Mitra Energi Persada Tbk and the official website of the Indonesian stock exchange. The data analysis technique used is the normality test, linearity test, heteroscedasticity test, simple linear regression test, coefficient of determination test, and hypothesis testing. The results of the t test show that the profitability variable has no positive and significant effect on firm value. It can be seen from the significant value of 0.420 <0.05 t-count 0.824 <t-table 1.734, it can be concluded that Ho is rejected and Ha is accepted.